Modeling Health Risk Factors in Russia Using Input-Output and Econometric Approaches (Baltic Journal of Real Estate Economics and Construction Management, 2013)
The article analyzes particular reasons (risk factors) that cause the deterioration of public health. Much attention is paid to the ecological factor. The maximum permissible concentration of harmful substances in the atmosphere and water reservoirs is exceeded in practically all the cities in Russia. 1The present research attempts to give not only analytical, but also quantitative assessment of the influence of various factors (with the help of regression analysis) on the health condition of Russian citizens. With the help of a CAIIN 2 model complex, a forecast for the ecological-economic development of the Russian Federation by the year 2015 has been made. The forecast helped to estimate the influence of the ecological factor on the sickness rate.